Amino Acid profile evaluation on Argentinean on farm sampled soybean - Accoroni, Cecilia; Magnano, Luciana; Enrico, Juan Martin; Santos, Diego Jose; Mir, Leticia Raquel; Conde, María Belén; Chialvo, Eugenia; Orlando, Ángela; Rossi, Rodolfo (Donau Soja, 2024)
Poster